Effects of different drying methods on quality changes and energy characteristics of tilapia fillets. Issue 3 (2nd July 2020) - Wei, Linbao; Qiu, Weiqiang; Jin, Yingshan; Zheng, Ruilin; Row, KyungHo; Cheng, Yudong; Jin, Yinzhe
Abstract: The effects of different drying methods (hot air drying (HAD), microwave drying (MD), and hot air-microwave combined drying (HAMCD) processes) on the drying characteristics, rehydration ability, colour, texture, moisture state, microstructure, and energy characteristics of tilapia fillets have been investigated. The best rehydration and recovery ratios of tilapia fillets were obtained using HAMCD (58.96 and 39.24%, respectively). Tilapia fillets quickly become a burnt-yellow colour by MD. HAMCD can improve the hardness, chewiness, and elasticity values, and can obtain crispy tilapia fillets. In the moisture state peak image, the symmetry of the T21 (fixed water) peak obtained at 70 °C + 250 W (H3M) was the best with an asymmetry factor (As) of 1.04. In the MRI image, the brightness of the proton density weighted image was arranged from high to low as follows: HAD > HAMCD > MD. Using SEM, the microstructure of the tilapia fillets prepared using HAMCD showed a large number of small holes. The specific energy consumption was reduced ∼1.8 fold and the thermal efficiency increased ∼5 fold using HAMCD when compared with the HAD process. It was concluded that HAMCD can be used for to process tilapia fillets with high quality and low operating costs.